Odpowiedzi

2009-12-10T15:15:44+01:00
3x-3y+4x=8
3x-15y=5-9y

7x-3y=8 |*(-2)
3x-6y=5

-14x+6y=-16
3x-6y=5

-11x=-11 |*(-11)
x=1

3x-3y+4x=8
3*1-3y+4*1=8
3-3y+4=8
-3y=-3-4+8
-3y=1 |:(-3)
y=-1/3

Licze na max pkt za zadanko z góry dzieki:D
2009-12-10T15:16:09+01:00
3(x-y)+4x=8
3(x-5y)=5-9y
3x - 3y + 4x = 8
3x - 15y = 5 - 9y
7x - 3y = 8 mnożymy przez - 2
3x - 6y = 5
-14x + 6y = -16
3x - 6y = 5
- 14x + 3x = -16 + 5
-11x = -11
x = 1
3x - 6y = 5
3 - 6y = 5
- 6y = 5 - 3
- 6y =2
y = - 1/3
x = 1
y = - 1/3